2013
DOI: 10.1021/ja405843r
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Intramolecular (3 + 1) Human Telomeric G-Quadruplex Bound to a Telomestatin Derivative

Abstract: Guanine-rich human telomeric DNA can adopt secondary structures known as G-quadruplexes, which can be targeted by small molecules to achieve anticancer effects. So far, the structural information on complexes between human telomeric DNA and ligands is limited to the parallel G-quadruplex conformation, despite the high structural polymorphism of human telomeric G-quadruplexes. No structure has been yet resolved for the complex with telomestatin, one of the most promising G-quadruplex-targeting anticancer drug c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 69 publications
5
174
1
Order By: Relevance
“…G4 structure stabilization was recorded for sanguinarine in a considerably stronger extent than berberine. The ∆T m of F21T varied considerably in presence of these three alkaloids, although molecular modeling methods suggest almost the similar mode of interactions and comparable binding energies in the hybrid 3+1 topology [64]. Non-electrostatic interactions in the binding of small molecules to G4 are preferable for telomerase inhibition under physiological conditions [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G4 structure stabilization was recorded for sanguinarine in a considerably stronger extent than berberine. The ∆T m of F21T varied considerably in presence of these three alkaloids, although molecular modeling methods suggest almost the similar mode of interactions and comparable binding energies in the hybrid 3+1 topology [64]. Non-electrostatic interactions in the binding of small molecules to G4 are preferable for telomerase inhibition under physiological conditions [60].…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid 3+1 topology of intramolecular telomeric quadruplex (PDB id 2MB3) was used as the starting point to study G4-ligand interactions [64]. The docking and molecular dynamics protocol was adapted from Ohnmacht et al [39].…”
Section: Molecular Dynamics (Md) Simulationsmentioning
confidence: 99%
“…More recently a series of macrocyclic molecules (telomestatin analogues) have been developed, with improved features over telomestatin parental structure (Granzhan et al 2010). Macrocyclic hexaoxazole L2H2-6 M (2) OTD is such a derivative of telomestatin which interact with G-quadruplex by p-stacking and electrostatic interactions (Chung et al 2013) telomestatin is currently under clinical trials (Kim and McAlpine 2013). Daunomycin (Fig.…”
Section: Compounds Targeting Telomeric Dna G-quadruplex Ligandsmentioning
confidence: 99%
“…Finally, by combining the structural aspects of T4 and Telomestatin, Nagasawa et al made T9, which had a better potency in stabilizing the G-quadruplex than the one of T4 [67]. Resolving the structure of a complex formed between T9 and human telomeric G-quadruplex DNA, Nagasawa et al concluded that the analogue interacted with the G-quadruplex via p-stacking and electrostatic interactions [68].…”
Section: Telomestatinmentioning
confidence: 99%